"Even through text, there is that connection": user experiences on chat and text hotlines for intimate partner violence and sexual assault - Wood, Leila (Journal of family violence, 2025)
Purpose: Providers focused on intimate partner violence (IPV) and sexual assault have increasingly added chat/text components to their phone hotline services. Despite increasing use of chat/text modalities on violence-focused hotlines, little is known about their use, especially with respect to user perspectives and experiences. Methods: Data are from an evaluation of chat/text hotline services at a large community-based IPV and sexual assault agency in the southwest U.S. Interviews (n = 16) and surveys (n = 171) with service users, and chat/text transcripts (n = 396) were data sources for this study. Results: The following four themes articulate user-defined service experiences: 1) Chat/text hotlines can offer a safer way to reach out for help, especially when phone calls are not an option; 2) Relative to voice calls, chat/text hotlines create a more accessible modality of support for some survivors and community members; 3) Chat/text hotline staff foster support and connection; and 4) Chat/text hotline staff provide resources and guidance needed to address impacts of violence and prevent future harm. While chat/text hotline users overwhelmingly had positive experiences, service user experiences were dampened when staff skills and/or resource access were perceived as inadequate. Conclusions: Survivor interviews and chat/text transcripts demonstrate the positive impact of these options for enhancing survivor access to resources, providing additional safe avenues for service engagement, and meeting survivor needs for an empathic, quick connection with an advocate. Training, resource support, and adequate staffing on chat/text hotlines can enhance survivor experiences and improve safety outcomes.